Pendampingan Pengelolaan Jurnal Online di Universitas Selamat Sri (UNISS) Kendal - Nur Khasanah; Hery Mustofa; Adzhal Arwani Mahfudh; Syaiful Bakhri (Universitas Semarang, 2023)
The existence of scientific journals is fundamental as a place for the publication of scientific articles for academics to show the results of their research work. Along with the development of technology and information, it demands the management of online-based journals for the convenience and transparency of the articles in them. Management of journals with an online system is still not fully understood by academics in several institutions. As one of the universities located not far from UIN Walisongo Semarang, Selamat Sri University (UNISS) Kendal has sufficient resources and according to needs to be a place for community service activities to be carried out with the theme of assisting in the management of online journals based on the Open Journal System (OJS). The purpose of this assistance is to introduce online scientific journal management using the OJS system at UNISS. The method used is lectures and hands-on practice regarding online journal management. The results of this community service activity are knowing information about the availability of infrastructure, articles, Human Resources (HR), and regulations that support the start of managing online journals using OJS. In addition, understanding and awareness of the need to have online journals for the benefit of scientific publications for researchers or academics are also obtained which is the requirement as stated in the Tri Dharma of Higher Education.